Lactiplantibacillusplantarum HM-P2 influences gestational gut microbiome and microbial metabolism - Liu, Bin; Zhang, Zhenzhen; Zhao, Junying; Li, Xianping; Wang, Yaru; Liu, Lu; Qiao, Weicang; Chen, Lijun (Frontiers in Nutrition, 2024)
IntroductionHuman milk-derived probiotics are beneficial bacteria that provide gestational health benefits, for both pregnant women and their offspring. The study aims to investigate whether the administration of human milk-derived probiotic L. plantarum HM-P2 could effectively influence gestational health.MethodsThe gestational humanized microbiome model was built by fecal microbiome transplant from gestational women into germ-free (GF) mice.ResultsHM-P2 was successfully planted and increased the top crypt depth of the colon, and microbes such as L. reuteri,Anaerofilum sp. An201, and Gemmiger were up-regulated in the HM-P2 group throughout gestation. HM-P2 significantly promoted the contents of intestinal caproic acid, bile acids, and tryptophan catabolites such as serotonin. Gut microbes were associated with these bile acids and tryptophans.DiscussionHM-P2 could modulate the microbial community and microbial metabolites in gestational humanized GF mice. This probiotic strain could be a potential gestational dietary supplement with health benefits.